Rembuk Tani Wujud Pendampingan, Solidaritas Sosial Hippa Dan Gapokta - Salim Ashar (IAI Darussalam, 2022)
The emergence of this research was caused by researchers' anxiety related to agricultural issues in Sudimoro Village, namely the lack of awareness of farmers regarding the pattern of irrigation distribution in Sudimoro village. To unravel this, it is necessary to find a solution to overcome it. The approach used is the constructivism paradigm with social solidarity theory by Emile Durkheim and James S. Coleman's rational choice. The results showed that a lack of communication between farmers caused a lack of awareness among the farmers so they did what they wanted without coordinating with the irrigation of icers. Therefore, the solution of ered for creating mutual benefits is to take a community service approach, mingle with farmers, and hold deliberations before going down to the fields to introduce modern (data-based) methods by HIPPA and GAPOKTAN assistants. With this activity it is hoped that it can solve the problems faced by farmers, aiming to see local wisdom and the uniqueness of nature that God has bestowed to be managedproperly and correctly, with the concept Nature, God and Humans are interrelated.